Takhrij and Syarah Hadith of Agrotechnology: Recommendations for Eating Dates - Hany Fahimatul Fa’iq; Wahyudin Darmalaksana; Suryaman Birnadi (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding the recommendation to eat dates. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this research is that the content of dates has many benefits, especially in the health sector. The conclusion of this research is takhrij and syarah hadith of the Prophet. about dates with agrotechnology analysis informs that the content of dates is not only a hunger delay but there are many other benefits that can be obtained by consuming them.